Molecular investigation of hormonal alterations in Oreochromis niloticus as a bio-marker for long-term exposure to zinc oxide nanoparticles. Issue 1 (1st January 2021) - Alkaladi, Ali; Afifi, Mohamed; Ali, Haytham; Couderchet, Michel
Abstract : This study aimed to investigate the potential effects of long-term zinc oxide nanoparticles' (Zn-ONPs) exposure to the hormonal profile of O. niloticus and their application as a bio-marker for fresh water pollution by Zn-ONPs. Two hundred-forty female O. niloticus were used. Growth hormone (GH), thyroid stimulating hormone (TSH), triiodothyronine (T3), tetraiodothyronine (T4), follicular stimulating hormone (FSH), luteinizing hormone (LH), estradiol (E2), glucagon, insulin, Adrenocorticosteroid hormone (ACTH) serum concentrations and the expression levels of GH, insulin-like growth factor gene (IGF-I), insulin and insulin receptor A (IRA) genes were determined. The levels of GH, TSH, FSH, LH, T3, T4, Estradiol, E2, insulin and GH, IGF-I, insulin and IRA genes expression decreased significantly in Zn-ONPs' exposed fish in a concentration-dependent manner; meanwhile, serum ACTH and cortisol increased. The alterations in hormone levels and their gene expressions are considered as good bio-markers for the detection of fresh water pollution with Zn-ONPs.